The feasibility of preventing Hospital-Acquired Pressure Ulcers (HAPUs) - Ahmalia, Renty (Journal of health research and technology, 2025)
Introduction: Hospital-acquired pressure ulcers (HAPUs) are a significant healthcare issue, leading to physical complications, extended hospital stays, and increased healthcare costs. Preventive measures are crucial for managing this problem. With the growing integration of technology in healthcare, mobile e-book applications and chatbots offer promising tools for improving clinical practice and decision-making. This study evaluates the feasibility of using these technologies in terms of the Technology Acceptance Model (TAM), focusing on perceived usefulness, ease of use, and intention to use among nurses. Methods: A quantitative research design was employed to assess the perceptions of 30 registered nurses working in a hospital setting. The Technology Acceptance Model (TAM) framework guided the measurement of key variables, including perceived usefulness, ease of use, and intention to use. Data were collected through a self-administered online survey and semi-structured interviews. Descriptive statistics and thematic analysis were used to analyze the data. Results: The study revealed positive perceptions of the chatbot and mobile e-book app in terms of their usefulness, ease of use, and intention to use. The mean scores for usefulness, ease of use, and intention to use were 16.55 ± 1.50, 17.32 ± 0.79, and 13.03 ± 1.74, respectively, indicating high feasibility for adoption. Discussion: The findings suggest that mobile e-books and chatbots are well-received by healthcare professionals, with perceived usefulness and ease of use being significant factors for their adoption. These technologies can support clinical decision-making, reduce medical errors, and improve healthcare outcomes. Future developments should focus on integrating these tools into healthcare training programs and enhancing their functionality with real-time updates and interactive features. Keywords: Hospital-acquired pressure ulcers, Technology Acceptance Model, mobile e-books, chatbots, healthcare technology.